Why am I learning English? Spanish EFL sports science university students´ motivational orientations through the prism of the L2 motivational self system - Bobkina, Jelena; Gómez-Ortiz, María-José; Núñez del Río, María Cristina; Sastre-Merino, Susana (Studies in Second Language Learning and Teaching, 2021)
The study explores the motivational profiles of Spanish EFL sports science university students from the second language (L2) motivation self system (L2MSS) perspective to ultimately support Spanish higher institutions´ plans committed to improving employability and competitiveness. The study analyzes the relationships between L2 motivation, L2 proficiency, gender, and L2 contextual variables using data from 196 English as a foreign language (EFL) sports science university students. The data reveal that the ideal L2 self construct stands out as the most salient and powerful factor, while the ought-to and rebellious L2 selves are less significant and there are items loading on both of them at the same time. Thus, higher means for the ideal L2 self motivation correspond to higher levels of L2 proficiency and are supported by L2 learning contextual variables. The strongest ought-to L2 self was registered in students with mid-low L2 proficiency and a lack of L2 learning experiences. Meanwhile, the rebellious L2 self is clearly distinguishable only for students with high L2 proficiency. Pedagogical and curricular implications of these findings are that the ideal and the rebellious L2 selves could positively predict students´ L2 proficiency. Thus, new dynamics of education should explore language teaching methodologies that are more likely to enhance students´ ideal and rebellious L2 selves.